2004
DOI: 10.1291/hypres.27.227
|View full text |Cite
|
Sign up to set email alerts
|

Hyperuricemia and Cardiovascular Risk Factor Clustering in a Screened Cohort in Okinawa, Japan

Abstract: The relation between serum uric acid level and cardiovascular risk factors is complex and has been investigated mainly in men. We examined the correlation between serum uric acid level and obesity, hypertension, dyslipidemia, and diabetes mellitus (DM) in both men and women of a screened cohort in Okinawa, Japan. A total of 9,914 individuals (6,163 men and 3,751 women ranging in age from 18 to 89 years) who were screened at Okinawa General Health Maintenance Association were subjects in this study. Hyperuricem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
108
7
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(144 citation statements)
references
References 37 publications
25
108
7
4
Order By: Relevance
“…This is mostly because serum uric acid is associated with other cardiovascular risk factors, such as hypertension 25 and dyslipidemia. 9 In the current study, we also found positive correlations between uric acid and BMI, blood pressure, and triglycerides, and a negative correlation between uric acid and HDL-C. It is also suggested that hyperuricemia is a marker for insulin resistance, an underlying condition of the metabolic syndrome, and that the association between hyperuricemia and cardiovascular disease may be secondary to this association.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This is mostly because serum uric acid is associated with other cardiovascular risk factors, such as hypertension 25 and dyslipidemia. 9 In the current study, we also found positive correlations between uric acid and BMI, blood pressure, and triglycerides, and a negative correlation between uric acid and HDL-C. It is also suggested that hyperuricemia is a marker for insulin resistance, an underlying condition of the metabolic syndrome, and that the association between hyperuricemia and cardiovascular disease may be secondary to this association.…”
Section: Discussionsupporting
confidence: 77%
“…[1][2][3] Possible explanations for this link may include elevation of uric acid, a natural antioxidant 4,5 as a defense mechanism against advanced atherosclerosis, 6 or hyperuricemia-induced endothelial dysfunction 7 and facilitation of smooth muscle cell proliferation. 8 However, on the other hand, many studies argue that the observed association between uric acid and atherosclerosis is attributable to an indirect association of hyperuricemia with cardiovascular risk factors 9 or clustering of these metabolic and hemodynamic risk factors, designated "metabolic syndrome." 10,11 Although many studies have focused on the presence or absence of an independent relationship between uric acid and coronary and cerebrovascular artery diseases, [12][13][14] thus far, few have examined the independence of the relationship between serum uric acid and carotid atherosclerosis.…”
mentioning
confidence: 99%
“…A total of 200 of asymptomatic hyperuricemia cases were ascertained according to the criteria of a serum uric acid concentration Ͼ7.0 mg/dL (416.4 mol/L) for males or Ͼ6.0 mg/dL (356.9 mol/L) for females, which is commonly used in clinical laboratories and has been proposed in previously published studies to defi ne hyperuricemia (11,12). Of the cases, 13 were excluded due to: (1) those with incomplete self-reported hyperuricemia or gout; (2) those who were taking medications for hyperuricemia or gout; (3) those with hypertension, diabetes, renal failure, lymphoproliferative and myeloproliferative diseases.…”
Section: Major Dietary Patterns and Risk Of Asymptomatic Hyperuricemimentioning
confidence: 99%
“…MetS is characterized by the presence of multiple common cardiovascular risk factors, such as central obesity, atherogenic dyslipidemia (hypertriglyceridemia and low high-density lipoprotein cholesterol (HDL-C)) levels, hyperglycemia and elevated blood pressure (BP). Elevated SUA levels are prevalent in patients with hypertension 1,2 and MetS, [3][4][5][6][7] and these levels can be a significant predictor of the development of hypertension 3,[8][9][10] and MetS. [11][12][13][14] Although evidence has suggested that elevated SUA levels might have a role in hypertension, 15 a causal relationship has not been established.…”
Section: Introductionmentioning
confidence: 99%